The Effectiveness of South Korean Government Policies in Addressing the Low Fertility Rate Crisis: A Human Development Approach and Impact Evaluation - Alya Nadzira; Abrar Arkeisha; Nursabilah Aisyah; Nasution Sartika; Mahadiansar Mahadiansar (International Journal of Social and Political Sciences, 2026)
South Korea’s fertility decline has become a demographic and policy challenge because it is closely connected to population aging, labour shortages, welfare sustainability, gender inequality, and weakening confidence among young adults in forming families. Using a qualitative descriptive method based solely on secondary data, this study analyzes academic literature, government policy documents, demographic statistics, OECD reports, Statistics Korea publications, and studies on family policy, childcare, housing, employment, and work–family balance. The findings show that South Korea’s low fertility rate is shaped by structural factors, including employment insecurity, unaffordable housing, high education costs, long working hours, unequal care responsibilities, and career penalties for women after childbirth. Government responses, including financial incentives, childcare subsidies, parental leave, housing support, and work–family balance policies, demonstrate increasing policy adaptability but remain limited in their long-term effectiveness. Financial support may reduce immediate household burdens, yet it cannot sufficiently transform the deeper institutional and cultural conditions that discourage marriage and childbearing. From a human development perspective, effective fertility policy must expand people’s freedom to form families under secure, equal, and supportive conditions. The study concludes that South Korea’s demographic recovery requires integrated structural reform that strengthens gender equality, accessible childcare, affordable housing, employment security, reproductive autonomy, and a family-supportive welfare system.